Analisis Orientasi Kewirausahaan Dan Keunggulan Bersaing Terhadap Kinerja UKM Gerai Dekranasda Kabupaten Sukabumi - Aslia, Farisa; Sunarya, Erry; Norisanti, Nor (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study is to determine the influence of entrepreneurial orientation and competitive advantage on the performance of SMEs. The objects in this study are entrepreneurial orientation (variable X1), competitive advantage (X2), and SME performance (variable Y). The research method used is quantitative, descriptive and associative methods. In this study using sampling techniques non-probability sampling by method sampling saturated with a total sample of 84 UKM owners registered at the Dekranasda outlet in Sukabumi District. The data analysis technique used is multiple linear regression. The results of the research based on the simultaneous test (F test) and partial test (T test) show that entrepreneurial orientation and competitive advantage have a significant effect on the performance of SMEs. The contribution of entrepreneurial orientation and competitive advantage to the performance of SMEs is 65.3% while the remaining 34.7% is the influence of other factors outside of this study.